Improving The Quality Of Mathematics Learning Through Strengthening Pedagogical Competencies, Effectiveness Of Project Based Learning, Creativity And Achievement Motivation - Andi Hermawan; Briliantina Indrati; Eni Susanti (EDUCATION JOURNAL OF INDONESIA, 2024)
The intensity of systemic linkages and synergy of teachers, students, curriculum and learning materials, media, facilities and learning systems in producing optimal learning processes and outcomes in accordance with curricular demands, this is what is meant by quality of learning. The quality of learning is an important element related to achieving educational goals. From various educational development reports, it is known that the quality of mathematics learning at private vocational schools in Bogor Regency is not as expected, both for educational goals and competency demands. Therefore, research is needed to obtain information on variables related to improving the quality of learning. The aim of this research is to carry out strategies and ways to improve the quality of learning by conducting research on the influence of the variables of pedagogical competence, effectiveness of project based learning (PjBL), creativity, achievement motivation and learning quality. This research uses the path analysis method to determine the influence between the variables studied and the SITOREM method for indicator analysis to obtain strategies and ways to improve the quality of learning. Keyword : Quality of Learning, Pedagogical Competency, Effectiveness of Project Based Learning (PjBL), Creativity, Achievement Motivation, SITOREM Analysis. Keywords: Quality of Learning, Pedagogical Competency, Effectiveness of Project Based Learning (PjBL), Creativity, Achievement Motivation, SITOREM Analysis.